Transgenic sorghum : effects of altered kafirin synthesis on kafirin polymerisation, protein quality, protein body structure and endosperm texture - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.